Anisotropic lithosphere under the Fennoscandian shield from P receiver functions and SKS waveforms of the POLENET/LAPNET array - POLENET/LAPNET Working Group; Vinnik, Lev; Kissling, Eduard; id_orcid:0 000-0001-9575-7951 (Tectonophysics, 2014)
ISSN:0040-1951 ISSN:1879-3266